Australia's National Biosolid Research Program - how it came about, and what has it discovered? - McLaughlin, M.; Warne, M.; Stevens, D.; Whatmuff, M.; Heemsbergen, D.; Broos, K.; Barry, G.; Bell, M.; Nash, D.; Pritchard, Deborah; Penney, N. (International Water Association, 2007)
The National Biosolids Research Program (NBRP) was established by the CSIRO Centre for Environmental Contaminants Research in 2002 in order to coordinate research relating to the benefits and risks of using biosolids for Australian agriculture. Prior to the establishment of the NBRP, research on biosolid use in agriculture had been concentrated in one state (New South Wales), with pockets of uncoordinated activity in other states. The NBRP is a coalition of seven research agencies around Australia, with support from several metropolitan and regional water authorities, and from several state environmental and natural resource management agencies. In terms of potential environmental risks, the NBRP initially concentrated onmetals and focussed field experimentation on cadmium, copper and zinc. The research has subsequently moved onto examining potential risks from pathogens, pharmaceuticals, endocrine disrupting compounds and personal care products. As well as potential risks, the benefits of nutrients and organic matter in biosolids on crop growth are also being assessed, with various cropping systems around Australia being evaluated.